2016
DOI: 10.1007/s00464-016-4849-2
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of bariatric surgery in the young: a single-institution experience caring for patients under 21 years old

Abstract: LGBP and LSG seem to confer comparable weight loss benefit in patients ≤21 years old with acceptable surgical morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 40 publications
0
8
0
1
Order By: Relevance
“…Current evidence has not established a reduction in adverse CV events with rigorous control of CV risk factors in adolescents with T2DM. Several studies have reported that typically less than a third of these patients achieve their glycaemic or lipid targets and are less likely to be prescribed lipid lowering treatments, reninangiotensin-system inhibitors or anti-platelet agents than T2DM patients presenting in later life [140][141][142][143] .…”
Section: Pharmacological Approachesmentioning
confidence: 99%
“…Current evidence has not established a reduction in adverse CV events with rigorous control of CV risk factors in adolescents with T2DM. Several studies have reported that typically less than a third of these patients achieve their glycaemic or lipid targets and are less likely to be prescribed lipid lowering treatments, reninangiotensin-system inhibitors or anti-platelet agents than T2DM patients presenting in later life [140][141][142][143] .…”
Section: Pharmacological Approachesmentioning
confidence: 99%
“…3840 Moreover, we identified baseline sex and race disparities and lower-than-expected proportion of adolescent bariatric surgery cases in males and minorities. Our study did not demonstrate racial disparities in outcomes, including weight loss and remission of ORCs.…”
Section: Resultsmentioning
confidence: 99%
“…25 Even though there were no randomized studies, a metaanalysis confirmed the effectiveness of SG for weight loss in obese adolescents. 22 Although several studies seemed to show that SG provided results similar to those of RYGB, 10,18,26 others found that weight loss after SG was better than with LAGB. 25,27 Obesity is associated with several comorbidities in adolescents and young adults.…”
Section: Discussionmentioning
confidence: 99%